Performance Analysis of Hybrid Power Plant (Wind and Solar) in Baron Techno Park Gunung Kidul Yogyakarta - Mychel Gatriser Pae; Ridwan Budi Prasetyo; Suharyanto Suharyanto; T. Haryono (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2017)
Renewable energy is generated through the conversion process of energy sources which are abundant in the earth such as wind, sun, heat, rain, geothermal, hydro, ocean water and others into an environmentally friendly form of energy. This kind of energy does not cause negative effects to the environment when being used. Therefore, by using renewable energy, the earth is not polluted. This is a major step in controlling global warming, which is one of the elements that leads to environmental degradation. The use of renewable energy sources is indispensable. One great opportunity for future renewable energy is the integration of various sources of energy (hybrid power plant). This paper presents the analysis performance of hybrid power plant (wind and solar) installed in the area of Baron Techno Park. Modeling with HOMER (Hybrid Optimization Model for Electric Renewable) Version 3.8.1 was done with two conditions, first was a grid connected and the second was an off-grid condition. The first system modeling for the installed system capacity NPC and COE had the lowest price for the off-grid condition being $ 62.020 and - $ 0.0213. For the $ 4,910.37 / year was system operating cost. For this capacity, electricity that was connected into grid up to 152.473 kWh / year. The second modeling systems was done with generating capacity in operating. Unknown NPC price was $ 20,887.76 and the COE was - $ 0,021 for grid connected system condition. Operational cost up to $1,685.87 / year, and electricity production being was 63,55 kWh / year.     With the grid, the contribution of Baron Techno Park hybrid power plants could lower carbon dioxide gas up to 82.63 kg/year for operating systems and 202.63 kg/year for systems with installed capacity.